2006
DOI: 10.1063/1.2184307
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and simulations of the ablation stage of wire arrays with different initial wire sizes

Abstract: Comparisons of 20mm diameter, 300-wire tungsten arrays with different initial wire sizes were made on the 20MA Sandia Z facility. Radiographic measurements of each wire array, taken at the same point in the current during the wire ablation stage, show systematic differences. A detailed comparison of the radiography and self-emission data with simulations and analytic models suggests that a variation in the mass ablation rate with wire size may be responsible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…Tungsten wire arrays are used much more commonly in large scale z-pinch driven experiments and have therefore been investigated in a great deal more detail. 9,[11][12][13][14] The dynamics observed in the experiments presented in this paper proved to be very different from those observed in the aluminium experiments. The formation of collisional structures was not observed; instead the electron density distributions varied smoothly between the ablation streams and inter-wire gap regions.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Tungsten wire arrays are used much more commonly in large scale z-pinch driven experiments and have therefore been investigated in a great deal more detail. 9,[11][12][13][14] The dynamics observed in the experiments presented in this paper proved to be very different from those observed in the aluminium experiments. The formation of collisional structures was not observed; instead the electron density distributions varied smoothly between the ablation streams and inter-wire gap regions.…”
Section: Introductionmentioning
confidence: 84%
“…[14][15][16] This paper presents both quantitative and structural data on this behaviour. We present the results of these experiments alongside calculations of the expected collisional mean free paths for these plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Previous estimates 16,17 of collisional mean free paths for these experiments have indicated that while each ablation streams should be selfcollisional, the approach velocity between counter propagating Tungsten ablation streams has to be large enough that they should interpenetrate without significant collisional interaction. Although interferometric imaging is sensitive only to the free electron density of the plasma, the mass discrepancy between the ions and the electrons means that the ion component of the plasma carries the vast majority of the momentum; over the spatial scales resolvable in our experiment, the free electron distribution is forced by the constraints of quasineutrality (k De $ lm) to reflect the underlying ion density distribution.…”
Section: Interferometric Evidence Of Changes In Collisional Dynamicsmentioning
confidence: 97%
“…Aluminum and tungsten wire arrays were investigated; previous calculations [15][16][17] had indicated that while the ablation streams produced by aluminum arrays should mostly interact collisionally, those produced by tungsten arrays should remain collisionless for a significant portion of the experiment.…”
Section: Interferometric Evidence Of Changes In Collisional Dynamicsmentioning
confidence: 99%
“…11 were diagnosed through x-ray backlighting with the aid of a streak camera. More modern techniques involves the use of a backlight x-ray plus Bragg crystals, 26,27 giving a resolution of about 10-20 m. Another interesting technique is tunable diode laser absorption, which might allow simultaneous measurement of the FIG. 5.…”
Section: B Proposed Experimental Setupmentioning
confidence: 99%